Fides quaerens intellectum, hindu divine philosophy and its relevance to religious moderation in Indonesia - Avalokitresvari, Ni Nyoman Ayu Nikki; Paul, Sanghati (Life and Death: Journal of Eschatology, 2025)
Background: The relationship between faith and reason has been a topic of interest in both religion and philosophy. In the Western tradition, they are often viewed as distinct and difficult to reconcile. However, Hinduism emphasizes the synthesis of ritual (karmakāṇḍa) and knowledge (jñanakāṇḍa), which integrates human intellect with divine understanding. Objective: This paper explores the concept of faith and reason in both Western and Hindu philosophy, specifically looking at how these ideas are interconnected and how they influence the development of global citizenship, unity, and interfaith harmony. Methods: The study uses a comparative approach, analyzing key figures such as St. Anselm in Christian philosophy and Ādi Śaṅkarācārya and Swami Vivekananda in Hindu philosophy. The research examines their ideas on the synthesis of faith, reason, and intellect. Findings: The findings show that in both traditions, faith and reason are not mutually exclusive but are complementary. St. Anselm’s Fides quaerens intellectum and Śaṅkarācārya’s doctrine of unity promote a harmonious relationship between theology and philosophy, suggesting that reason and intellect strengthen faith and belief. Conclusion: The synthesis of faith and reason in both Western and Hindu philosophy supports the development of a global citizen who embraces diversity without conflict. Both traditions emphasize the importance of human intellect and reasoning in spiritual practice and understanding, highlighting the universal value of unity. Novelty/Originality of this article: This paper presents a unique comparative analysis of faith and reason in Western and Hindu philosophy, emphasizing their complementary roles in fostering interfaith dialogue, intellectual growth, and global citizenship.